ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA FRAUD PADA LAPORAN KEUANGAN PERUSAHAAN PUBLIK DI INDONESIA - Nawangsari, Ajeng Tita; Amala, Sabitha Aksanu (Jurnal Riset Ilmu Akuntansi, 2026)
This study aims to analyze the factors influencing the occurrence of fraud in financial statements of public companies in Indonesia using a literature review approach. Employing the Fraud Triangle, Fraud Diamond, and Agency Theory as conceptual frameworks, this research synthesizes findings from previous empirical studies and relevant academic sources. The results reveal that financial pressure, weak internal control, moral justification (rationalization), and individual capability to exploit system weaknesses are the main factors driving financial statement fraud. Moreover, corporate governance mechanisms and board independence play a crucial role in reducing fraud risk. This research contributes theoretically to the development of forensic accounting knowledge and provides practical recommendations to enhance transparency and accountability in corporate financial reporting.